Effect of occupational exposure to welding fumes and noise on heart rate variability: An exposed-unexposed study on welders and airport workers' population - David Lucas; David Lucas; François Guerrero; Emmanuel Jouve; Sophie Hery; Pascale Capellmann; Jacques Mansourati; Jacques Mansourati (Frontiers Media S.A., 2022)
IntroductionWelding fumes (WF) are a complex mixture of gas and particles. Action of occupational exposure to WF on cardiovascular system has been recently studied as for noise.Research questionThe main objectives of our study are therefore to evaluate the impact of exposure to WF, noise, and combined WF and noise on autonomic nervous system as assessed by heart rate variability (HRV).MethodsThe study groups were 16 welders and eight airport workers (as a control group). All the participants underwent ambulatory electrocardiogram, personal WF, and noise exposure monitoring, respectively, with dust track and calibrated noise dosimeter during workday. Atmospheric environmental assessments at workplaces have been also performed. HRV parameters were summarized for all the workday and hourly. Correlation tests were used to examine relation between HRV parameters and levels of noise exposure in the two population. Analysis of covariance (ANCOVA) was used for mean of each HRV parameters.ResultsFor HRV parameters, we found significant higher levels for mean range of high frequency (HF), standard deviation of normal-to-normal R-R interval (SDNN), and root mean square of successive heartbeat interval difference (RMSSD) in welders which suggested an imbalance between sympathetic and parasympathetic nervous system in this population. For relation between noise and HRV parameters, we noted that levels of low frequency (LF), HF, and SDNN were significantly correlated with mean noise levels for welders (respectively, r = 0.62, r = 0.357, r = 0.48), not in control group. Using ANCOVA, we found that working as a welder significantly increases mean of HF (p = 0.01) and RMSSD (p = 0.02) and decreases in LF/HF (p = 0.008). Indeed, the interaction between exposure to WF and mean noise levels for HF (p = 0.005), LF/HF (p = 0.01), and RMSSD (p = 0.007) was significant.ConclusionThis study shows an impact of WF and noise on ANS balance. One hypothesis is WF exposure could increase sensibility to noise exposure on autonomic nervous system or there is a synergic effect.